DIGITAL-BASED LEARNING TRANSFORMATION: INNOVATION AND CHALLENGES IN THE SOCIETY 5.0 ERA - Saepullah Saepullah; Muhammad Yusup; Nashihun Amin; Deni Rudini; Kasmin Kasmin (International Journal of Teaching and Learning, 2025)
The rapid development of digital technology has significantly transformed the education sector, particularly in the Society 5.0 era, which emphasizes human-centered innovation through advanced digital integration. Digital-based learning has emerged as a crucial innovation, enhancing educational accessibility, flexibility, and efficiency. This study examines the transformation of digital-based learning, highlighting both its innovations and challenges. Using a mixed-method research approach, quantitative data from educational institutions and surveys are analyzed to assess improvements in learning outcomes, while qualitative insights from interviews with educators and students provide a deeper understanding of opportunities and obstacles in digital learning implementation. The findings indicate that digital-based learning has expanded access to quality education through e-learning platforms, artificial intelligence-driven personalized learning, and virtual reality-enhanced interactive experiences. Additionally, it has facilitated adaptive learning, enabling students to progress at their own pace and fostering collaborative learning environments through digital communication tools. However, challenges such as digital divide, technological disparities, cybersecurity risks, and resistance to change remain significant barriers. Addressing these challenges requires collaborative efforts from governments, educational institutions, and technology providers to establish policies and infrastructures that ensure inclusive and sustainable digital education. In conclusion, digital-based learning serves as a transformative force in modern education, offering innovative solutions to enhance learning experiences. Nevertheless, achieving its full potential necessitates addressing existing challenges through equitable access to technology, teacher training, and robust digital policies.